Association of miRNA-146a rs2910164 and miRNA-196 rs11614913 polymorphisms in patients with ulcerative colitis: A meta-analysis and review. Issue 39 (September 2018) - Li, Zhongyi; Wang, Yao; Zhu, Yi
Abstract: Background: It has been reported that the single nucleotide polymorphisms (SNPs) miRNA-196 (miR-196) rs11614913 and miRNA-146a (miR-146a) rs2910164 are related to susceptibility to ulcerative colitis (UC). Because the previously reported results have been mixed and uncertain, the aim of this study was to perform a meta-analysis and review to assess the relationship between these 2 SNPs and UC risk. Methods: In this analysis, 5 studies involving 1023 cases and 1769 controls for miR-196 rs11614913 and 4 studies involving 827 cases and 1451 controls for miR-146 rs2910164 were included. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were used to pool the effect size. Results: A decreased risk of UC was identified in homozygote comparison (GG vs CC: OR = 0.69, 95% CI: 0.52–0.93, P = .02), recessive comparison (GG vs CG + CC: OR = 0.74, 95% CI: 0.59–0.92, P = .007), and dominant comparison (GG + CG vs CC: OR = 0.79, 95% CI: 0.65–0.97, P = .02) of miR-146 rs2910164 in Asian but not Caucasian population. No evidence of an association was shown between the rs11614913 polymorphism and UC risk in allelic, heterozygote, homozygote, recessive, and dominant models in both Caucasian and Asian populations ( P > .05). Conclusions: MiR-146 rs2910164, but not miR-196 rs11614913, was associated with a decreased risk of UC in Asian population. However, the results should be treated with caution because of the limited sample size and heterogeneity. Well-designed studies with large sample sizes and more ethnic groups are needed to validate the risks identified in the current meta-analysis and review.